Characterization of fine particulate matter from indoor cooking with solid biomass fuels. (18th November 2022) - Eriksson, Axel; Abera, Asmamaw; Malmqvist, Ebba; Isaxon, Christina
Abstract: Household burning of solid biomass fuels emits pollution particles that are a huge health risk factor, especially in low‐income countries (LICs) such as those in Sub‐Saharan Africa. In epidemiological studies, indoor exposure is often more challenging to assess than outdoor exposure. Laboratory studies of solid biomass fuels, performed under real‐life conditions, are an important path toward improved exposure assessments. Using on‐ and offline measurement techniques, particulate matter (PM) from the most commonly used solid biomass fuels (charcoal, wood, dung, and crops residue) was characterized in laboratory settings using a way of burning the fuels and an air exchange rate that is representative of real‐world settings in low‐income countries. All the fuels generated emissions that resulted in concentrations which by far exceed both the annual and the 24‐hour‐average WHO guidelines for healthy air. Fuels with lower energy density, such as dung, emitted orders of magnitude more than, for example, charcoal. The vast majority of the emitted particles were smaller than 300 nm, indicating high deposition in the alveoli tract. The chemical composition of the indoor pollution changes over time, with organic particle emissions often peaking early in the stove operation. The chemical composition of the emitted PM is different for different biomass fuels, which is important to consider both in toxicological studies and in source apportionment efforts. For example, dung and wood yield higher organic aerosol emissions, and for dung, nitrogen content in the organic PM fraction is higher than for the other fuels. We show that aerosol mass spectrometry can be used to differentiate stove‐related emissions from fuel, accelerant, and incense. We argue that further emission studies, targeting, for example, vehicles relevant for LICs and trash burning, coupled with field observations of chemical composition, would advance our understanding of air pollution in LIC. We believe this to be a necessary step for improved air quality policy.